The Influence of Organizational Culture and Leadership on Student Organizational Performance through Work Commitment (JED (Jurnal Etika Demokrasi), 2024)
Organizational work commitment can be the main driver of organizational performance. Through this commitment, organizational members will be more motivated to achieve common goals and contribute optimally. This research aims to analyze the role of work commitment as a mediator in influencing organizational culture and organizational leadership on the performance of student organizations. The survey method was used to collect data based on purposive sampling from 55 members of DEMA FTIK at IAIN Ponorogo who were involved in the organizational leadership program. Data collection was carried out using a questionnaire consisting of a 5-point Likert scale. PLS-SEM analysis was used to analyze data and test the conceptual model. Data analysis techniques include statistical tests to test relationships and mediation. The research results show that organizational performance is significantly influenced by organizational culture (β=0.426; ρ=0.002) and organizational leadership (β=0.264; ρ=0.037). However, work commitment does not mediate a significant influence on organizational culture and organizational leadership on organizational performance. The implication of these findings is the need for special attention to the development of organizational culture and leadership that supports work commitment to improve organizational performance. Recommendations are given to implement cultural development strategies and leadership training to strengthen the work commitment of student organization members in higher education.